Prabowo Gibran's Local Language Campaign On The Tiktok Account Fillixpratama - Wiratno, Esa Prasetyo; Rozi, Fakhrur (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
This research analyzes the impact of the local language campaign conducted by Prabowo Gibran through the TikTok account @fillixpratama25, which demonstrates adaptation to digital trends and the preferences of young voters. Unlike previous studies that focused on political image and campaign strategies in other contexts, this research offers a new approach by emphasizing the use of local language on TikTok. The methodology used is a qualitative approach with a constructivist paradigm, utilizing field research methods. Data was collected through direct observation, document analysis, and interviews with relevant stakeholders. Critical discourse analysis by Teun A. van Dijk was used to understand how local language in this campaign builds or undermines social dominance and reflects power structures. The results of the study indicate that the use of local language and a relaxed communication style create emotional closeness with the audience, increase political awareness among young voters, and leverage the viral potential of TikTok to expand the reach of political messages. This campaign combines media ecology theory and social media campaign theory, highlighting how new media transforms the political communication environment and enables more direct interaction between politicians and the public. The conclusion shows that adaptive strategies in using social media with relevant local languages can strengthen the connection between candidates and voters, increase political awareness, and open new opportunities in political communication in the digital era.